Biogenic silica accumulation and diatom assemblage variations through the Eocene-Oligocene Transition: a Southern Indian Ocean versus South Atlantic perspective - Bryłka, Karolina; Witkowski, Jakub; Bohaty, Steven M. (Palaeogeography, palaeoclimatology, palaeoecology, 2024)
It is widely interpreted that there is a significant link between climate cooling at the Eocene-Oligocene Transition (EOT; ∼34 Ma) and subsequent diatom proliferation in the world's oceans during the mid to late Cenozoic. Yet, our understanding of biogenic silica flux through the EOT interval is based on limited data from a few sites, and there are many complications in making a meaningful comparison based on biogenic silica concentration data generated using different techniques. Here, we present new biogenic opal flux and diatom assemblage records across EOT from Ocean Drilling Program Site 748 (Southern Kerguelen Plateau, southern Indian Ocean), in addition to new biogenic opal flux records from the South Atlantic (Deep Sea Drilling Project Site 511, Falkland Plateau and Ocean Drilling Program Site 1090, Agulhas Ridge). Observed opal flux shifts and variability at Site 748 are consistent with published data from nearby Site 744; both sites show considerable shifts in biogenic opal accumulation rates corresponding to shifts in published benthic oxygen isotope records through the EOT. In contrast, our new opal flux record for Site 511, derived from biogenic opal concentration measurements via spectrophotometry, differs from the published record derived from insoluble residues, whereas new data generated for Site 1090 are generally consistent with previously published flux reconstructions. The South Atlantic biogenic opal flux records, however, are dissimilar from one another, and both are dissimilar from the Southern Indian Ocean records. Also, the taxonomic composition of the diatom assemblages from Sites 511, 748 and 1090 display considerable differences, with hemiauloids and rhizosolenids - generally inferred as indicative of oligotrophic conditions - being the dominant diatoms at the Southern Kerguelen Plateau (Site 748). Published records show that hemiauloid taxa are absent from the earliest Oligocene interval at Site 1090, which is widely seen as a record of deposition from nutrient-rich waters sustaining abundant diatom assemblages. These differences in diatom assemblages testify to regional differences in nutrient concentrations. In particular, the timing of biogenic opal flux pulses between Sites 1090 and 748 imply a shift in the locus of opal deposition to areas further south in the Southern Ocean across the EOT, likely related to proto-ACC development and strengthening of frontal boundaries. Thus, combined geochemical and micropaleontological evidence points to a regionally variable rather than a global, unified opal flux response to climate cooling through the Eocene-Oligocene Transition.